2010
DOI: 10.1101/gr.101469.109
|View full text |Cite
|
Sign up to set email alerts
|

Examination of transcriptional networks reveals an important role for TCFAP2C, SMARCA4, and EOMES in trophoblast stem cell maintenance

Abstract: Trophoblast stem cells (TS cells), derived from the trophectoderm (TE) of blastocysts, require transcription factors (TFs) and external signals (FGF4, INHBA/NODAL/TGFB1) for self-renewal. While many reports have focused on TF networks that regulate embryonic stem cell (ES cell) self-renewal and pluripotency, little is know about TF networks that regulate self-renewal in TS cells. To further understand transcriptional networks in TS cells, we used chromatin immunoprecipitation with DNA microarray hybridizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
128
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(135 citation statements)
references
References 57 publications
(78 reference statements)
7
128
0
Order By: Relevance
“…It was recently reported that Gata3 and Cdx2 act in concert to induce the expression of common and independent target genes in the trophoblast lineage [35]. Moreover, transcription factors including GATA3 occupy regulatory regions of a number of target genes in TS cells [41]. GATA factors may interact alone or in combination with other transcription factors at the regulatory regions of trophoblast-specific factor genes, which in turn determine timing and degree of trophoblastspecific factor expression in trophoblast cells.…”
Section: Bai Et Al 524mentioning
confidence: 99%
“…It was recently reported that Gata3 and Cdx2 act in concert to induce the expression of common and independent target genes in the trophoblast lineage [35]. Moreover, transcription factors including GATA3 occupy regulatory regions of a number of target genes in TS cells [41]. GATA factors may interact alone or in combination with other transcription factors at the regulatory regions of trophoblast-specific factor genes, which in turn determine timing and degree of trophoblastspecific factor expression in trophoblast cells.…”
Section: Bai Et Al 524mentioning
confidence: 99%
“…S6). The signals over all targets were normalized and averaged to represent the overall distribution of the binding pattern for all targets of a given factor (Methods; Kidder and Palmer 2010). To assign a binding site to an annotated gene, we first collected coding and non-coding gene annotations from WormBase 170 and 200, respectively, while miRNAs were collected from miRBase v14 (Gerstein et al 2010).…”
Section: Calling Target Coding and Non-coding Genesmentioning
confidence: 99%
“…However, to date, even the defining characteristics of such a human TSC remain controversial. Many genes have been designated, based on rodent studies, as required for establishment of the trophoblast lineage and/or maintenance of TSCs, including Cdx2, Elf5 and Eomes Niwa et al, 2005;Donnison et al, 2005;Ng et al, 2008;Russ et al, 2000;Kidder and Palmer, 2010). Some studies have identified the mRNA for these genes in human trophectoderm or primary trophoblast, and fewer have indisputably confirmed presence of the corresponding proteins in this compartment (Adjaye et al, 2005;Hemberger et al, 2010;Niakan and Eggan, 2013); even fewer studies have shown a definite role for these gene products in human trophoblast proliferation and/or differentiation.…”
Section: Introductionmentioning
confidence: 99%